PETROLOGICAL MODEL OF THE FORMATION OF SULFIDE DEPOSITS - Marakushev A.A.; Paneyakh N.A.; Zotov I.A. (My University, 2007)
Sulfide deposits differ from other ore deposits in their high Fe contents, which could not be provided by any other endogenic process except magmatism. Transmagmatic fluids with hydrogen sulfide and ore metals, which migrate from the core, serve as a link between the last process and sulfide ore formation. Under their influence, Fe-rich magmatic differentiates lose their stability and are subjected to sulfurization with the input of Cu and chalcophile metals, which make up the basis of sulfide ore formation. In terms of the composition of Cu-associated metals, sulfide ore formation is divided into copper–nickel and copper–zinc (massive sulfide) types. Such division is related to the universal mafic–ultramafic fractionation of primary mantle magmas and the consequent compositional differentiation of their ferruginous derivates (magnesian derivative in ultramafic settings and virtually Mg-lacking derivative in mafic environments).